Green low-carbon concrete and preparation method thereof

By adopting a gelling material system with all solid waste low-carbon raw materials in cement cementitious materials, and through efficient grinding and heating stable treatment, low-carbon composite gelling materials are formed, the problem of low-carbon utilization rate in the existing technology is solved, and low-carbon production and efficient and economical concrete preparation are achieved.

CN119638279APending Publication Date: 2025-03-18CHINA STATE CONSTR READY MIXED CONCRETE CO LTD +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411444096.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, rice husk ash, dust-collecting stone powder and steel slag powder have low utilization rates in cement cementitious materials, resulting in a decrease in strength and high cost of concrete.

Method used

A gelling material system based on all solid waste low-carbon raw materials is adopted, and the gelling and heating of the high-efficiency ball mill is milled to form a low-carbon composite gelling material, and combined with sulfate exciter and polycarboxylic acid water reducing agent to optimize the gelling property and strength of the gelling system.

Benefits of technology

It has achieved low-carbon production of concrete, reduced carbon emissions by more than 80%, reduced unilateral costs by 30%, and met the requirements of construction performance and mechanical properties, which have significant economic benefits and environmental value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses green low-carbon concrete, which is prepared from the following raw materials in parts by weight: 100 to 140 parts of rice hull ash, 140 to 180 parts of dust collection stone powder, 100 to 140 parts of steel slag powder, 780 to 880 parts of sand, 950 to 1100 parts of stone, 4 to 10 parts of exciting agents, 6 to 10 parts of water reducing agents and 170 to 180 parts of water. Wherein the rice hull ash, the dust collection stone powder and the steel slag powder are subjected to grinding, heating and stabilizing treatment to form the low-carbon composite cementing material. A full-solid waste raw material system based on the rice hull ash, the dust collection stone powder and the steel slag powder is adopted, high-energy grinding and heating stabilization treatment are sequentially carried out, a low-carbon composite cementing material with high activity is formed, meanwhile, the exciting agent is combined, and the adverse effect of alkali silicate reaction brought by the rice hull ash on the system can be effectively inhibited; the obtained concrete has good working performance, mechanical performance and the like, and the related preparation method is relatively simple, convenient to operate, relatively low in cost and suitable for popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building materials, and specifically relates to green low-carbon concrete and a preparation method thereof. Background Art

[0002] With the rapid development of global industrialization, the amount of industrial solid waste has increased dramatically. How to effectively treat and utilize these solid wastes has become an environmental problem that needs to be solved urgently. Rice husk ash, dust stone powder, and steel slag powder are three typical industrial solid wastes. Their large accumulation not only occupies precious land resources, but also may cause serious pollution to the surrounding environment. Therefore, it is particularly important to develop a technology that can convert these solid wastes into high-value-added products.

[0003] At present, the utilization rate of the above three solid waste materials as cement binders is low. The main reasons include low activity, poor cementitiousness, limited filling benefits, etc. For example, the allowable filling amount of rice husk ash is small, generally less than 25% of the mass of the filled material, and it can usually only play a supplementary role in reducing costs; in addition, once the filling amount is large, the reinforcement effect will be significantly reduced; the activity of dust-collected stone powder is significantly lower than that of cement clinker, so the cement clinker participating in the initial hydration will be reduced, resulting in problems such as reduced strength of concrete. Summary of the invention

[0004] The main purpose of the present invention is to provide a new type of green low-carbon concrete to address the problems of urban solid waste disposal, high carbon emissions of raw materials in commercial concrete, high costs, etc., by adopting a cementitious material system based on all-solid waste low-carbon raw materials such as rice husk ash, dust stone powder, and steel slag powder, which can achieve low-carbon production of concrete and take into account good working performance and mechanical properties; and the preparation method involved is relatively simple, easy to operate, low cost, and suitable for popularization and application.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A green low-carbon concrete, the raw materials and their weight proportions include: 100-140 parts of rice husk ash, 140-180 parts of dust-collected stone powder, 100-140 parts of steel slag powder, 780-880 parts of sand, 950-1100 parts of stone, 4-10 parts of activator, 6-10 parts of water reducer, 170-180 parts of water; wherein, rice husk ash, dust-collected stone powder and steel slag powder are first ground and heat-stabilized to form a low-carbon composite cementitious material.

[0007] In the above scheme, the SiO2 content in the rice husk ash is greater than 85%, the activity index is greater than 90%, and the median particle size D50 is less than 6 um.

[0008] In the above scheme, the dust collecting stone powder has a 45um sieve fineness of 9-13%, a 28d activity index greater than 70%, and a water requirement ratio of 95-105%.

[0009] In the above scheme, the median particle size D50 of the steel slag powder is less than 5um, the 28d activity index is greater than 70%, and the specific surface area is greater than 450m 2 / kg.

[0010] In the above scheme, the rotation speed adopted in the grinding step is greater than 500r / min, the grinding time is 3 to 5h, and the ball-to-material ratio is 10 to 15:1.

[0011] Furthermore, after grinding, the obtained powder is subjected to a heating stabilization treatment and then cooled to obtain a low-carbon composite gelled material.

[0012] In the above scheme, the temperature of the heat stabilization treatment is 110-150° C. and the time is 2-6 hours.

[0013] In the above scheme, the activator is a sulfate activator, and specifically gypsum or sodium sulfate can be selected.

[0014] In the above scheme, the fineness modulus of the sand is 2.5-2.8, the sand is medium in the second zone; the stone is 5-25mm continuously graded, and the needle-like content is less than 6%.

[0015] In the above scheme, the water reducing agent has a water reducing rate of 15 to 25%.

[0016] The above-mentioned method for preparing green low-carbon concrete comprises the following steps:

[0017] 1) Weighing of raw materials, each raw material and its weight proportion include: 80-120 parts of rice husk ash, 120-160 parts of dust collecting stone powder, 80-120 parts of steel slag powder, 780-880 parts of sand, 950-1100 parts of stone, 4-10 parts of activator, 6-10 parts of water reducer, and 170-180 parts of water;

[0018] 2) Mix the weighed rice husk ash, steel slag powder and dust-collected stone powder, grind them, heat and stabilize them, and cool them to obtain a low-carbon composite cementitious material;

[0019] 3) First, mix part of the water and the water reducer evenly to obtain a water reducer solution, add the water reducer solution into a mixer, add the low-carbon composite gelling material, and then add the activator under stirring;

[0020] 4) Continue to add sand and stone in sequence under stirring conditions, stir and add remaining water in this process, that is, low carbon early strength concrete.

[0021] In the above scheme, in step 3), 40-70% of water is first added.

[0022] In the above scheme, the stirring condition of step 3) is continuous stirring for 2 to 3 minutes, and the stirring treatment time of step 4) is continuous stirring for 3 to 5 minutes.

[0023] The green low-carbon concrete prepared according to the above scheme has an initial slump of 160 to 200 mm, an initial expansion of 220 to 250 mm, a 3d compressive strength greater than 17 MPa, and a 28d compressive strength greater than 42.5 MPa.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1) The present invention adopts a full solid waste gelling system based on rice husk ash, dust stone powder and steel slag powder. First, a high-energy ball mill is used for grinding to increase its specific surface area and reaction activity, thereby promoting the formation of silicate ions (SiO3 2- ) and calcium ions (Ca 2+ ) to form calcium silicate compounds; at the same time, chemical changes are promoted between the three solid wastes, so that the resulting mixture has good gelling properties; the ground mixture is then subjected to heat stabilization treatment, which can increase the chemical structure stability of the material and promote the stability of the gelling properties.

[0026] 2) After the cementitious system (low-carbon composite cementitious material) of the present invention is dissolved in water, the calcium hydroxide produced by the hydrolysis of the dust collecting stone powder can effectively stimulate the active ingredients such as silicon dioxide and aluminum oxide in the rice husk ash and steel slag powder, which can promote the system to further form a hydrated calcium silicate product with cementitious properties and provide the main strength for the cementitious system.

[0027] 3) Steel slag powder and sulfate activators can be combined to effectively inhibit the adverse effects of alkali-silicate reaction brought by rice husk ash on the system; the hydration reaction process and hydration products of steel slag powder can reduce the alkalinity in the system, and the sulfate activator can not only promote the hydration of steel slag powder, but the sulfate ions therein can also exchange with the alkali ions in the system to further reduce the content of free alkali.

[0028] 4) The cementitious material in the system of the present invention is composed of all solid waste raw materials. Compared with conventional concrete, the carbon emission of concrete prepared by this system can be reduced by more than 80%, the unit cost of concrete can be reduced by 30%, and the construction performance and mechanical properties meet the requirements, which has obvious economic benefits and environmental protection value. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] In the following examples, the rice husk ash used was taken from a biomass power plant in Huanggang City, Hubei Province; wherein the SiO2 content was 88%, the 28d activity index was 91%, and the median particle size D50 was 4.9 um.

[0031] The dust-collecting stone powder used comes from Huaxin Cement Co., Ltd., with a fineness of 11.6%, a 28d activity index of 73%, and a water demand ratio of 101%.

[0032] The steel slag powder used has a median particle size D50 of 4.2um, a 28d activity index of 74%, and a specific surface area of ​​475m 2 / kg.

[0033] The polycarboxylate water-reducing agent used is manufactured by China Construction Western Construction New Materials Technology Co., Ltd. The model is ZJC-01, with a water reduction rate of 23% and a solid content of 9.8%.

[0034] The sand used is quartz sand with a fineness modulus of 2.6, medium sand in zone 2; the stone is continuously graded from 5 to 25 mm, and the needle-like content is 5.8%.

[0035] Example 1

[0036] A green low-carbon concrete, the preparation method of which comprises the following steps:

[0037] 1) Weigh the raw materials, and the weight proportions of the raw materials are: 120 parts of rice husk ash, 160 parts of dust collecting stone powder, 120 parts of steel slag powder, 820 parts of sand, 1000 parts of stone, 6 parts of sodium sulfate, 8 parts of polycarboxylate water reducer, and 175 parts of water;

[0038] 2) Mix rice husk ash, steel slag powder and dust-collected stone powder according to the weighed proportion, and then place them in a high-efficiency ball mill for mechanical grinding for 4 hours. The speed of the ball mill is set to 600 r / min, steel balls are used as the ball material, and the ball-to-material ratio is 10:1. The ground mixture is stabilized in an oven at 110° C. for 2 hours, and then cooled to room temperature for standby use to obtain a low-carbon composite cementitious material;

[0039] 3) First, mix 70% of the total water with the water reducer to obtain a water reducer solution, add the water reducer solution into the mixer, and then immediately add the low-carbon composite cementitious material, start the mixer, and evenly add sodium sulfate while stirring. This process lasts for 2 minutes;

[0040] 4) After 2 minutes, add sand and gravel into the mixer, and stir again for 3 minutes. During this process, add the remaining water to obtain a low-carbon early-strength concrete mixture.

[0041] Example 2

[0042] A green low-carbon concrete, whose preparation method is roughly the same as that of Example 1, except that: the raw materials and their weight proportions are: 100 parts of rice husk ash, 170 parts of dust collecting stone powder, 130 parts of steel slag powder, 820 parts of sand, 1000 parts of stone, 6 parts of sodium sulfate, 8 parts of polycarboxylic acid water reducer, and 178 parts of water.

[0043] Example 3

[0044] A green low-carbon concrete, whose preparation method is roughly the same as that of Example 1, except that: the raw materials and their weight proportions are: 130 parts of rice husk ash, 160 parts of dust collecting stone powder, 110 parts of steel slag powder, 820 parts of sand, 1000 parts of stone, 6 parts of sodium sulfate, 8 parts of polycarboxylic acid water reducer, and 175 parts of water.

[0045] Comparative Example 1

[0046] A green low-carbon concrete, whose preparation method is roughly the same as that of Example 1, except that: the raw materials and their weight proportions are: 120 parts of rice husk ash, 160 parts of dust collecting stone powder, 120 parts of steel slag powder, 820 parts of sand, 1000 parts of stone, 0 parts of sodium sulfate, 8 parts of polycarboxylic acid water reducer, and 180 parts of water.

[0047] Comparative Example 2

[0048] A green low-carbon concrete, whose preparation method is roughly the same as that of Example 1, except that: the raw materials and their weight proportions are: 220 parts of rice husk ash, 180 parts of dust collecting stone powder, 0 parts of steel slag powder, 820 parts of sand, 1000 parts of stone, 6 parts of sodium sulfate, 8 parts of polycarboxylic acid water reducer, and 175 parts of water.

[0049] Comparative Example 3

[0050] A green low-carbon concrete, the preparation method of which is substantially the same as that of Example 1, except that the efficient grinding and heating stabilization treatment described in step 2) are not performed.

[0051] Comparative Example 4

[0052] A green low-carbon concrete, the preparation method of which is substantially the same as that of Example 1, except that the concrete is not placed in an oven for stabilization after efficient grinding.

[0053] Comparative Example 5

[0054] A green low-carbon concrete, whose preparation method is roughly the same as that of Example 1, except that in step 2), rice husk ash, steel slag powder, and dust-collected stone powder are first mixed according to the weighed proportions and then stabilized in an oven at 110° C. for 2 hours, and then placed in a high-efficiency ball mill for mechanical grinding for 4 hours.

[0055] The concrete obtained in Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to working performance and mechanical property tests, specifically including: measuring the initial fluidity and expansion of the fresh concrete, molding the prepared concrete into a 150mm×150mm×150mm test mold for testing the compressive strength of the concrete, and performing a compressive strength test after curing for 3d and 28d under standard curing conditions. The specific test data indicators are shown in Table 1 below.

[0056] Table 1 Performance test results of concrete obtained from examples and comparative examples

[0057]

[0058]

[0059] The present invention is not limited to the above-mentioned embodiments. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications are also considered to be within the scope of protection of the present invention. The contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field.

Claims

1. A green low-carbon concrete, characterized in that: The raw materials and their weight proportions include: 100-140 parts of rice husk ash, 140-180 parts of dust-collecting stone powder, 100-140 parts of steel slag powder, 780-880 parts of sand, 950-1100 parts of stone, 4-10 parts of activator, 6-10 parts of water reducer and 170-180 parts of water; wherein, rice husk ash, dust-collecting stone powder and steel slag powder are first ground and heat-stabilized to form a low-carbon composite cementitious material.

2. The green low-carbon concrete according to claim 1, characterized in that: The rice husk ash has a SiO2 content of more than 85%, an activity index of more than 90%, and a median particle size D50 of less than 6 um.

3. The green low-carbon concrete according to claim 1, characterized in that: The dust collecting stone powder has a 45um square hole sieve residue fineness of 9-13%, a 28d activity index greater than 70%, and a water requirement ratio of 95-105%.

4. The green low-carbon concrete according to claim 1, characterized in that: The steel slag powder has a median particle size D50 of less than 5 μm, a 28d activity index of more than 70%, and a specific surface area of ​​more than 450 m 2 / kg.

5. The green low-carbon concrete according to claim 1, characterized in that: The grinding step adopts a rotation speed of >500r / min, a grinding time of 3 to 5h, and a ball-to-material ratio of 10 to 15:

1.

6. The green low-carbon concrete according to claim 1, characterized in that: The temperature of the heat stabilization treatment is 110-150° C. and the time is 2-6 hours.

7. The green low-carbon concrete according to claim 1, characterized in that: The activator is a sulfate activator.

8. The green low-carbon concrete according to claim 1, characterized in that: The sand has a fineness modulus of 2.5 to 2.8, and is medium sand in zone 2; the stone is continuously graded from 5 to 25 mm, and the needle-like content is less than 6%.

9. The green low-carbon concrete according to claim 1, characterized in that: The water reducing agent has a water reducing rate of 15 to 25%.

10. The method for preparing green low-carbon concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weighing of raw materials, each raw material and its weight proportion include: 80-120 parts of rice husk ash, 120-160 parts of dust collecting stone powder, 80-120 parts of steel slag powder, 780-880 parts of sand, 950-1100 parts of stone, 4-10 parts of activator, 6-10 parts of water reducer, and 170-180 parts of water; 2) Mix the weighed rice husk ash, steel slag powder and dust-collected stone powder, grind them, heat and stabilize them, and cool them to obtain a low-carbon composite cementitious material; 3) First, mix part of the water and the water reducer evenly to obtain a water reducer solution, add the water reducer solution into a mixer, add the low-carbon composite gelling material, and then add the activator under stirring; 4) Continue to add sand and stone in sequence under stirring conditions, stir, and add remaining water in this process to obtain green low-carbon concrete.

Citation Information

Patent Citations

  • Non-cement green mortar by using steel slag as cementing material and fine aggregate and preparation method thereof

    CN105859229A

  • Concrete containing machine-processed gravel powder and dust collection stone powder and preparation method thereof

    CN106007579A

  • All-solid-waste high-performance concrete as well as preparation method and application thereof

    CN111393083A

  • Constructional cementing material and preparation method and application thereof, and concrete and preparation method thereof

    CN112537914A

  • Preparation method of concrete mixed with dust collection stone powder and mineral powder based on strength and chloride ion permeation resistance double indexes

    CN115745501A